PTH-132 Iron Deficiency Anaemia Nurse Led Clinic: Audit of 1st Year. (4th June 2013) - Daker, C; McAuley, H; Mason, I; Shepherd, T; Hamilton, M; Epstein, O; Murray, C
Abstract : Introduction: Iron deficiency anaemia accounts for 4–13% of gastrointestinal referrals occurring in 2–5% of adult men and post menopausal women. Current guidelines suggest that the work up of asymptomatic anaemia remains incomplete and often inappropriate with important diagnoses of malignancy and malabsorption being missed. In an effort to improve our handling of these patients from primary care and reconfigure services, a nurse led clinic was established in 2009 with the aim to provide rapid access to appropriate investigations and management. Methods: All clinic patients between 01/06/2009–05/07/2010 were included in the study. Patients were triaged into the clinic via the GP referral letter. End points examined were:patient demographics, anaemia, microcytosis and iron deficiency, whether oral iron preparations were being used, investigations (OGD/colonoscopy), wait times for investigations and pathology identified. Data were collected using patient notes, pathology results database, clinic letters and endoscopy reports. Anaemia was classified as an Hb of < 11.5g/dL. Results: 110 patients were included (no exclusions); 81 female and 29 male (73.6%, 43.2%).Age range 21 –90yrs, mean 57yrs, median 58yrs.62% were made up of men (29) and post-menopausal women (47); 33%(13) menstruating females with GI symptoms and 46%(21) menstruating females without GI symptoms.62% were in receipt of oral iron supplementation at referral.66% of referrals included the blood results revealing 92% anaemic; 54% microcytic; 50% iron deficient. This compared to 68% of patients anaemic bled in the clinic of whom 20% were not anaemic but on iron supplementation leaving 12% neither anaemic nor on iron supplements. Of those not on iron (42 –13men, 29 women)21% had renal disease (GRF < 60), 12(29%) were iron deficient, 10(24%)were iron deficient and anaemic.A total of 61 patients underwent endoscopic investigation (47post menopausal and male group; 6 menstruating females with GI symptoms and 8 menstruating females without GI symptoms).We identified 4 mailgnancies; 3 polyps, 3 colitics, 9 upper Gi pathologies (GAVE, varices, ulcers, small bowel Crohns), 2 with Helicobacter pylori infection and 5 with celiac disease.12 had gynaecological causes, 2 renal causes.46 resolved on oral iron and 8 needed parentral iron infusions. Mean time from clinic to investigation was 9.5 weeks (SD 14.8) and median 4.86 weeks. Conclusion: Of the cohort a total of 55%(61) underwent endoscopy with an overt GI pathology yield (deemed causative for the anaemia) in 26(42%).The nurse led clinic has facilitated a decreased waiting time to appropriate test so improving patient outcomes in terms patient satisfaction, time to diagnosis and management strategy implementation, decreased clinic and investigation waiting times, reduced pressure on physicians lists and most importantly morbidity and mortality. Disclosure of Interest: None Declared.